Knowledge about tuberculosis and infection prevention behavior: A nine city longitudinal study from India - Huddart, Sophie; Bossuroy, Thomas; Pons, Vincent; Baral, Siddhartha; Pai, Madhukar; Delavallade, Clara (Public Library of Science, 2018)
Improving patients’ tuberculosis (TB) knowledge is a salient component of TB control strategies. Patient knowledge of TB may encourage infection prevention behaviors and improve treatment adherence. The purpose of this study is to examine how TB knowledge and infection prevention behaviors change over the course of treatment.